Titik tengkar pesantren : resolusi konflik masyarakat pesantren - Farchan, Hamdan, 1971-; Syarifuddin, 1974- (Yogyakarta : Pilar Religia, 2005)
Conflict among the community of Islamic religious training centers in Indonesia
Daftar pustaka : p. 265-271
Keywords: Islam -- Indonesia; Indonesia -- Islam and politics